Feasibility of karisjaya egg-laying chicken agribusiness (case study approach) - Sundari, Ristina Siti; Supriadi, Fatimah Fajria; Umbara, Dona Setia (Universitas Musamus, Merauke, Papua, 2025)
Agribusiness is a unitary business activity that includes one or the entire production chain, product processing, and marketing, broadly concerning agriculture. This study aimed to calculate the feasibility of an independent laying chicken agribusiness that experiences production fluctuations. The study's results stated that the operating costs required for 10 years are IDR. 921,080,000. The income received by the laying chicken farmer Mr. Cucu Suryana in carrying out his laying chicken agribusiness is IDR 603,474,200 per two years of production. The NPV using a social discount rate of 18% shows that the NPV in strata I is IDR 74,808,684. The IRR shows a result of 21.24% using the Social Opportunity Cost of Capital (SOCC) of 18.00%; this means that IRR > SOCC, the investment made by farmers will return within 3.11 years, and Net B/C is 1.21%. So, the effort is worth continuing.